Changes in respiratory muscle and lung function following marathon running in man - Ross, E.; Middleton, N.; Shave, R.; George, K.; McConnell, A. (Journal of Sports Sciences, 2008)
Respiratory muscle fatigue has been reported following short bouts of high-intensity exercise, and prolonged, moderate-intensity exercise, as evidenced by decrements in inspiratory and expiratory mouth pressures. However, links to functionally relevant outcomes such as breathing effort have been lacking. The present study examined dyspnoea and leg fatigue during a treadmill marathon in nine experienced runners. Maximal inspiratory and expiratory pressure, peak inspiratory and expiratory flow, forced vital capacity, and forced expiratory volume in one second were assessed before, immediately after, and four and 24 hours after a marathon. During the run, leg effort was rated higher than respiratory effort from 18 through 42 km (P < 0.05). Immediately after the marathon, there were significant decreases in maximal inspiratory pressure and peak inspiratory flow (from 118 ± 20 cm H2O and 6.3 ± 1.4 litres/s to 100 ± 22 cm H2O and 4.9 ± 1.5 litres/s respectively; P < 0.01), while expiratory function remained unchanged. Leg maximum voluntary contraction force was significantly lower post-marathon. Breathing effort correlated significantly with leg fatigue (r = 0.69), but not inspiratory muscle fatigue. Our results confirm that prolonged moderate-intensity exercise induces inspiratory muscle fatigue. Furthermore, they suggest that the relative intensity of inspiratory muscle work during exercise makes some contribution to leg fatigue.